Bibliometric and visual analysis of membranous nephropathy literature from 2010 to 2023 - Chen, Yirui; Liu, Chen; Shen, Hongnan; Su, Pingping; Pang, Liang; Zeng, Congcong; Cheng, Jinguo (Frontiers in Pharmacology, 2024)
Background Membranous glomerulonephritis, also known as membranous nephropathy (MN), is a common cause of nephrotic syndrome in adults. Despite extensive research on MN, bibliometric studies on the subject are scarce. Therefore, this study aimed to provide a visual analysis of global trends in membranous nephropathy research over the past 13 years. Methods This study conducted a bibliometric and visual analysis of global trends in MN research from 2010 to 2023. Articles related to MN were retrieved from the Web of Science Core Collection (WoSCC) database. Tools such as CiteSpace and VOSviewer were utilized to analyze publications, countries, institutions, authors, publishing journals, co-cited references, and keywords to identify the current state and future trends in MN research. Results The analysis encompassed 1,624 publications, showing an annual increase from 2010 to 2023. The People’s Republic of China emerged as the most active country in this field, while France’s Sorbonne Universite and Institut National de la Sante et de la Recherche Medicale (Inserm) led in publication volume among academic institutions. Debiec Hanna stood out as the most prolific author. BMC Nephrology had the highest number of publications, making it the most favored journal in the field. The article with the greatest co-citation intensity was “Primary Membranous Nephropathy,” a review published in 2017. Conclusion This study shows that there has been increasing interest in membranous nephropathy over the past 13 years. The most frequently encountered keywords were “membranous nephropathy” “nephrotic syndrome,” and “glomerulonephritis.” Analysis of emerging terms indicated that “a2 receptor antibody,” “domain containing 7a,” and “t cell” may remain prominent subjects of research in the forthcoming years. The findings highlight key research trends and areas of interest that can inform researchers, clinicians, and policymakers about the current state of MN research and help guide future research directions and clinical practice.